2020
DOI: 10.1021/jacsau.0c00058
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GM3 Analogues Containing Monofluoromethylene-Linked Sialoside: Synthesis, Stereochemical Effects, Conformational Behavior, and Biological Activities

Abstract: Glycoconjugates are an important class of biomolecules that regulate numerous biological events in cells. However, these complex, medium-size molecules are metabolically unstable, which hampers detailed investigations of their functions as well as their potential application as pharmaceuticals. Here we report sialidase-resistant analogues of ganglioside GM3 containing a monofluoromethylene linkage instead of the native O -sialoside linkage. Stereoselective synthesis of CHF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…This strategy was first developed by Hashimoto et al [77] . and later employed for ganglioside synthesis by several groups, [78] including ours [79] . We have, for the first time, described this technique as a “glucosylceramide (GlcCer) cassette” strategy (Scheme 31B) [80]…”
Section: Synthesis Of Gangliosidesmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy was first developed by Hashimoto et al [77] . and later employed for ganglioside synthesis by several groups, [78] including ours [79] . We have, for the first time, described this technique as a “glucosylceramide (GlcCer) cassette” strategy (Scheme 31B) [80]…”
Section: Synthesis Of Gangliosidesmentioning
confidence: 99%
“…A separately synthesized sialoglycan donor was then coupled with the glucosyl Cer acceptor to afford the complete ganglioside skeleton. This strategy was first developed by Hashimoto et al [77] and later employed for ganglioside synthesis by several groups, [78] including ours. [79] We have, for the first time, described this technique as a "glucosylceramide (GlcCer) cassette" strategy (Scheme 31B).…”
Section: Strategies Of Ganglioside Synthesismentioning
confidence: 99%
“…Free carbohydrate molecules with unnatural moieties or an unusual branching pattern can be physiologically active yet metabolically stable, making them potentially useful for in vivo applications [ 114 , 115 ]. They may also be included in a glycan array to study glycoenzymes and glycan binding proteins [ 116 ].…”
Section: Manipulating Sialyltransferases At a Molecular Levelmentioning
confidence: 99%
“…In particular, C -glycosides exhibit high structural similarity to native glycans. , For example, we recently demonstrated that C -glycoside analogues of ganglioside GM3, especially molecules with a CHF -glycoside linkage, exhibit greater biological activity at the cell level than analogues with a CH 2 - or a CF 2 -linkage. Furthermore, their conformation is similar to that of native GM3 . However, despite many reports of synthetic methodology for C -glycosides, there are few efficient strategies for directly forming a C -glycosidic linkage (direct C-glycosylation) via intermolecular coupling reaction, like a standard O-glycosylation reaction.…”
mentioning
confidence: 99%
“…Furthermore, their conformation is similar to that of native GM3. 3 However, despite many reports of synthetic methodology for C-glycosides, there are few efficient strategies for directly forming a C-glycosidic linkage (direct C-glycosylation) via intermolecular coupling reaction, like a standard Oglycosylation reaction.…”
mentioning
confidence: 99%